Modulation of Eosinophil Functions by Nitric Oxide: Cyclic GMPdependent and -independent Mechanisms - Ferreira, Heloisa H.A.; Conran, Nicola; Antunes, Edson (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2006)
Recruitment of eosinophils into tissues is a feature of a variety of allergic diseases, including asthma and nasal allergy. Eosinophils secrete several preformed granule proteins (eosinophil peroxidase, major basic protein, eosinophil cationic protein and eosinophil-derived neurotoxin) and newly-generated substances (oxygen-derived toxic metabolites, lipid mediators, cytokines and chemokines), which may contribute to the exacerbation of the allergic diseases. In the past decade, NO has been recognized as a major immunomodulatory mediator of inflammatory responses, particularly in the lung, where it is believed to play a pivotal role in modulating pulmonary eosinophilia and airways hyperresponsiveness in both allergic animals and humans, as evidenced by functional, biochemical and immunohistochemical studies. The NOcGMP signaling cascade was initially implicated in the modulation of eosinophil functions; however, additional studies have demonstrated that direct cGMP-independent mechanisms may also play important roles in eosinophil functions. Much progress in understanding the influence of NO on eosinophil functions has been achieved with the use of selective and non-selective NOS inhibitors, as well as NO-donor compounds, along with NOS isoform gene knock-out mice. However, these studies have resulted in numerous controversies and conflicting findings, possibly as a consequence of the diversity of experimental models used, animal species employed, methods of immunization and challenge with allergens, amongst others. The present review summarizes the role of NO in modulating, in vivo and in vitro, eosinophil adhesion, chemotaxis, airways hyperresponsiveness and apoptosis, outlining the conflicting findings in the literature, with emphasis on the allergic inflammatory responses.
Keywords: chemotaxis